2021
DOI: 10.1038/s41525-021-00182-z
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing variants of uncertain significance for reclassification using a rule-based algorithm in inherited retinal dystrophies

Abstract: Inherited retinal dystrophies (IRD) are a highly heterogeneous group of rare diseases with a molecular diagnostic rate of >50%. Reclassification of variants of uncertain significance (VUS) poses a challenge for IRD diagnosis. We collected 668 IRD cases analyzed by our geneticists using two different clinical exome-sequencing tests. We identified 114 unsolved cases pending reclassification of 125 VUS and studied their genomic, functional, and laboratory-specific features, comparing them to pathogenic and lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 41 publications
0
24
0
1
Order By: Relevance
“…Philp and colleagues have developed and validated an algorithm termed "estimate of pathogenic probability" (EPP) that predicts the pathogenicity of VUS based on its prevalence, segregation and predicted effects on protein structure [63]. In addition, Iancu and colleagues have recently developed a strategy for the reclassification of VUS that considers five pathogenicity predictors, resulting in an algorithm able to correctly reclassify approximately 70% of VUS as pathogenic in validation datasets [64]. The ACMG algorithm has been updated to incorporate new evidence.…”
Section: Variants Of Uncertain Significance Assessmentmentioning
confidence: 99%
“…Philp and colleagues have developed and validated an algorithm termed "estimate of pathogenic probability" (EPP) that predicts the pathogenicity of VUS based on its prevalence, segregation and predicted effects on protein structure [63]. In addition, Iancu and colleagues have recently developed a strategy for the reclassification of VUS that considers five pathogenicity predictors, resulting in an algorithm able to correctly reclassify approximately 70% of VUS as pathogenic in validation datasets [64]. The ACMG algorithm has been updated to incorporate new evidence.…”
Section: Variants Of Uncertain Significance Assessmentmentioning
confidence: 99%
“…Up to 10 non-solved cases gained new insights due to the reevaluation of our prioritized variants. Our variant prioritization approach was also applied for VUS reclassification, a major challenge to unlock the diagnosis of rare pathologies [10,[55][56][57]. Indeed, in our IRD subcohort, top 5 genes with more deleterious variants in IRD solved cases, present a higher degree of uncertainty in variant annotation (proportion of VUS and deleterious variants) in unsolved IRD cases.…”
Section: Discussionmentioning
confidence: 99%
“…Variants are classified using ACMG guides. In the IRD subcohort, there were reported 100 VUS fulfilling these criteria [10] (Additional file 1:Table S7). Of these, 63 fulfilled criteria to be within the database generated in this work, and were still classified as VUS according to ACMG (information taken from VarSome at the time of the analysis).…”
Section: Vus Reclassificationmentioning
confidence: 99%
“…A recent study using a rules-based algorithmic approach showed that 125 VUS were reclassified in 114 unsolved rare inherited retinal dystrophy patients which helped in the diagnosis of the disease. It was shown using validation datasets that ~70% of VUS in these patients were reclassified as pathogenic [ 49 ].…”
Section: Reanalysis Methodologies Using Machine Learningmentioning
confidence: 99%